The effectiveness of storytelling in enhancing empathy in bilingual kindergarten students - Tetrawan, Adinda Daniel; Yulia Ayriza; Hadiana, Deni; Tri Anggono; Hana Ayu Amalia (Insight: Jurnal Ilmiah Psikologi, 2024)
The primary objective of this research was to investigate the influence of storytelling as a pedagogical approach on the development of empathy in a group of bilingual kindergarten students. To achieve this, an experimental research design was employed, utilizing a one-group pretest-posttest comparative methodology. The study involved 12 bilingual kindergarten students; all of them were part of the experimental group. An initial examination of descriptive statistical data revealed that the average pretest score was 43.08, which increased to 45.00 in the post-test, indicating a notable improvement in the student's scores. Further statistical analysis, specifically the Wilcoxon test, confirmed the significance of the impact of storytelling on the students' empathy levels. The test resulted in a significance value of p = 0.002 (p < 0.01), providing compelling evidence that storytelling as a teaching method had a substantial and positive effect on enhancing empathy in bilingual kindergarten students. These findings suggest that incorporating storytelling into the curriculum can be a valuable tool in nurturing empathy in young learners, with potential implications for enhancing their social and emotional development. Keyword: Language; empathy; storytelling; students; kindergarten; experiment.